Runaway : Gregory Bateson, the double bind, and the rise of ecological consciousness - Chaney, Anthony (University of North Carolina Press, 2017)
Blending intellectual biography with a reappraisal of the 1960s, Anthony Chaney uses Gregory Bateson's life and work to explore the idea that a postmodern ecological consciousness is the true legacy of the decade. Surrounded by voices calling for liberation of all kinds, Bateson spoke of limitation and dependence. But he also offered an affirming new picture of human beings and their place in the world.